The effectiveness of drawing occupation therapy on auditory hallucinations among patients with schizophrenia - Robby Prihadi Aulia Erlando; Wuryaningsih, Emi Wuri; Kusumaningsih, Amalia; Hikmah, Faiqotul (JOURNAL OF Mental Health Concerns, 2025)
Background: Hallucinations are symptoms of mental disorders that affect sensory perception and impair thought control, often leading to risky behaviors if not supported by family or friends. Purpose: To evaluate the effectiveness of occupational drawing therapy in reducing auditory hallucinations in patients with schizophrenia. Method: A qualitative case study aimed to examine changes in hallucinatory symptoms and the ability to control them through drawing occupational therapy. The intervention was conducted from January 25 to February 1, 2025, involving one patient who received daily sessions lasting 20–30 minutes. Instruments used included the Drawing Therapy SOP, Auditory Hallucination Rating Scale (AHRS), and a symptom observation sheet. Results: Before therapy, the patient's AHRS score was 19, and symptom observation was 12. After therapy, the scores decreased to 9 and 4, respectively. Conclusion: Drawing therapy helped divert attention from hallucinations, encouraged emotional expression, and reduced symptom intensity. Keywords: Hallucinations; Occupational Drawing Therapy; Schizophrenia.